NIMBY Clout on the 2011 Italian Nuclear Referendum - Giuseppe Pignataro; Giovanni Prarolo (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
This paper claims that the 2011 Italian referendum on nuclear power is taking shape as a clean laboratory for the measurement of one of the main aspects of the NIMBY (Not In My BackYard) issue. Since the citizens voted on the possibility for the government to set up new nuclear plants in well-known sites, we identify community preferences for their locations across Italian municipalities using the turnout rate. The Fukushima nuclear disaster that happened a few months before the referendum may have magnified negative attitudes toward nuclear power. Thus, taking into account regional and political features that may influence ideological aversion to nuclear power, we still find highly negative correlation between distance from nuclear sites and the turnout rate.
Keywords: D72; H41; Q48; 330